2017
DOI: 10.7205/milmed-d-16-00259
|View full text |Cite
|
Sign up to set email alerts
|

Return on Investment Analysis of Health Experts onLine at Portsmouth: A 2-Year Review of the Navy's Newest Teleconsultation System

Abstract: The HELP program produces considerable savings (both tangible and intangible) to the Military Healthcare System for small costs. It does this both by increasing access to care at previously inaccessibly remote medical treatment facilities and by consequently decreasing the forward provider's reliance on medical evacuation in questionable cases. This positive ROI was potentially underestimated as this analysis did not account for recapture of care that would otherwise have been sent to the civilian market. On t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Although we identified two studies reporting a process similar to eConsult in Finland in the early 1990s, the contemporary eConsult design was implemented in the early 2000s and was further developed in the 2010s in large-scale programme in Ontario and the USA. In addition, we identified three non-civilian eConsult programmes in the USA that provide access to specialist care for military personnel and their families 47 69–72…”
Section: Resultsmentioning
confidence: 99%
“…Although we identified two studies reporting a process similar to eConsult in Finland in the early 1990s, the contemporary eConsult design was implemented in the early 2000s and was further developed in the 2010s in large-scale programme in Ontario and the USA. In addition, we identified three non-civilian eConsult programmes in the USA that provide access to specialist care for military personnel and their families 47 69–72…”
Section: Resultsmentioning
confidence: 99%
“…It was well-integrated in the overseas military medical environment prior to restrictions being placed on travel due to a global pandemic, and is a model that could be applied to healthcare service in civilian settings as well. This low-bandwidth, secure system demonstrated increased access to care in a method that was both time-efficient and costsaving over the course of the 2 decades it has been used, and in various global settings [1,5,6,8].…”
Section: Discussionmentioning
confidence: 99%
“…A two-year review of HELP's return on investment (ROI) showed considerable savings (both tangible and intangible) to the Military Healthcare System for relatively minimal cost by decreasing the medical provider's reliance on medical evacuation, most often from a ship, in questionable cases utilizing a low bandwidth, asynchronous, and internet accessible teleconsultation system [6]. This review looked at the first two years of this relatively new platform, but with only 559 cases they were able to use a physician review panel with three independent reviewers to assess each case.…”
Section: A Scalable Platform: Growth Of Path Beyond the Pacificmentioning
confidence: 99%
“…The positive return on investment and cost savings from prevented aeromedical evacuation has previously been reported in military telemedicine. 14 The mobile eye care app prevented the need for aeromedical evacuation in 4 consults (14%; 95% CI, 0.7%-28%) and downgraded the category of precedence from urgent or priority to routine in 4 consults (14%; 95% CI, 0.7%-28%).…”
Section: Discussionmentioning
confidence: 99%